Epidemiological characteristics, antifungal susceptibility, and mortality factors of candidemia in adults at a tertiary teaching hospital in Zunyi, China (2016–2023) - Xianghao Chen; Meijing Shen; Qun Feng; Guangwu Yang; Rengui Tian; Shifei Yao; He Zha (BMC Infectious Diseases)
Abstract Background Candidemia, a common nosocomial bloodstream infection caused by Candida species, is associated with a high mortality rate. This study aimed to analyze the epidemiological characteristics, distribution of Candida species, antifungal susceptibility, and mortality risk factors of adult patients with candidemia in Zunyi, China. These findings are expected to inform treatment and prevention strategies for candidemia in this region. Methods Clinical data, Candida species, antifungal susceptibility profiles, and prognosis of 92 patients with candidemia at the First People’s Hospital of Zunyi (the Third Affiliated Hospital of Zunyi Medical University) from January 2016 to December 2023 were retrospectively analyzed. Univariate and multivariate logistic regression analyses were performed to analyze risk factors for patient death. Results Analysis of 92 candidemia cases revealed an average incidence of 0.19% and mortality rate of 35.87%. Candida albicans was responsible for 33.70% of the infections, whereas non-C. albicans accounted for 66.30% of the total. Non-C. albicans was dominated by C. parapsilosis (31.52%), Nakaseomyces glabratus (18.48%), and C. tropicalis (13.04%). The susceptibility of all Candida species to amphotericin B exceeded 96%. C. albicans and C. parapsilosis showed greater than 70% susceptibility to fluconazole, itraconazole, and voriconazole, whereas C. tropicalis showed less than 60% susceptibility to these antifungal agents. Among the 33 dead patients, C. albicans was associated with a higher mortality rate than non-C. albicans (P = 0.007). Logistic multiple regression analysis showed that cardiovascular disease (OR = 8.913, 95% CI: 1.463–54.289, P = 0.018), kidney disease (OR = 13.672, 95% CI: 2.025–92.326, P = 0.007), and antifungal drug treatment duration less than 7 days (OR = 10.694, 95% CI: 1.841–62.112, P = 0.008) were independent risk factors for mortality in adult patients with candidemia. Conclusions The mortality rate among patients with candidemia remains high with C. albicans is the predominant pathogen in Zunyi, China. Cardiovascular disease, kidney disease, and antifungal drug treatment duration less than 7 days were independent risk factors for mortality in adult patients with candidemia. Therefore, greater attention should be paid to adult patients with risk factors for mortality to improve the outcomes of adult candidemia.